Global evidence of rapid urban growth in flood zones since 1985 - Rentschler, Jun; Avner, Paolo; Marconcini, Mattia; Su, Rui; Strano, Emanuele; Vousdoukas, Michalis; Hallegatte, Stéphane (Nature (London), 2023)
Disaster losses are increasing and evidence is mounting that climate change is driving up the probability of extreme natural shocks 1 – 3 . Yet it has also proved politically expedient to invoke climate change as an exogenous force that supposedly places disasters beyond the influence of local and national authorities 4 , 5 . However, locally determined patterns of urbanization and spatial development are key factors to the exposure and vulnerability of people to climatic shocks 6 . Using high-resolution annual data, this study shows that, since 1985, human settlements around the world—from villages to megacities—have expanded continuously and rapidly into present-day flood zones. In many regions, growth in the most hazardous flood zones is outpacing growth in non-exposed zones by a large margin, particularly in East Asia, where high-hazard settlements have expanded 60% faster than flood-safe settlements. These results provide systematic evidence of a divergence in the exposure of countries to flood hazards. Instead of adapting their exposure, many countries continue to actively amplify their exposure to increasingly frequent climatic shocks. Analysis of high-resolution annual data shows that global human settlements have expanded continuously and rapidly into flood zones, with those in the most hazardous zones increasing by 122% from 1985 to 2015.